Korupsi sebagai Kesalahan Administratif yang Menimbulkan Kerugian Keuangan Negara - Hukunala, Sandy Victor; Ajawaila, Della Paula (Universitas Negeri Malang, 2023)
This study aimed to analyze corruption as an administrative error that causes state losses. This analysis was another perspective that arises as a result of the Supreme Court's Cassation Decision regarding the BLBI fund corruption case. The type of research used in this study was normative legal research that focuses on doctrinal law, which examines and analyzes the provisions of the applicable laws and regulations relating to the issues being examined. The study results showed that if there was a loss to state finances due to an administrative error, the government official concerned was obliged to return the state financial loss no later than 10 days after it was decided and the results of supervision were issued. However, the return of state financial losses did not eliminate the punishment of criminals.